The role of public investment funds in driving Saudi vision 2030’s societal transformation - Oraby, Salah Ahmed; Khars, Murtadha Abdulhameed Mohammed Al (Edelweiss Applied Science and Technology, 2025)
In 2016, Saudi Arabia launched Vision 2030, which aims to shift the country beyond oil dependency. Vision 2030 is based on three main themes, one of which is the concept of a 'Vibrant Society,' which aims to strike a balance between development and preserving Saudi Arabia’s cultural, religious, and national traditions. This research explores how the Public Investment Fund (PIF) contributes to achieving the "A Vibrant Society" theme under Saudi Arabia’s Vision 2030 by applying change management strategies, digital transformation, stakeholder engagement, and transformational leadership. This study adopts a mixed-methods approach. It integrates quantitative survey data collected from 211 participants, which were statistically analyzed using Smart PLS, along with qualitative insights from expert interviews across multiple sectors. These insights were analyzed using thematic pattern analysis. Digital transformation and leadership are the most influential enablers of societal transformation, while structured change management and stakeholder engagement also play essential roles. The data relied on self-reported perceptions, which may be influenced by optimism bias. The sample, though sufficient, may not fully represent all key stakeholder groups involved in PIF’s projects.